2023
DOI: 10.3934/publichealth.2023055
|View full text |Cite
|
Sign up to set email alerts
|

The quiet quitting scale: Development and initial validation

Petros Galanis,
Aglaia Katsiroumpa,
Irene Vraka
et al.

Abstract: <abstract><sec> <title>Introduction</title> <p>COVID-19 pandemic causes drastic changes in workplaces that are likely to increase quite quitting among employees. Although quiet quitting is not a new phenomenon, there is no instrument to measure it.</p> </sec><sec> <title>Objective</title> <p>To develop and validate an instrument assessing quiet quitting among employees.</p> </sec><sec> <title>Methods</title> <p&g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…In our study, Cronbach's alpha for the factors "responses to moral adversity", "personal integrity", "relational integrity", and "moral efficacy" were 0.665, 0.782, 0.783, and 0.765, respectively. We used the Quiet Quitting Scale (QQS) to measure levels of quiet quitting among nurses [50]. The QQS has a three-factor structure: detachment (four items), lack of initiative (three items), and lack of motivation (two items).…”
Section: Methodsmentioning
confidence: 99%
“…In our study, Cronbach's alpha for the factors "responses to moral adversity", "personal integrity", "relational integrity", and "moral efficacy" were 0.665, 0.782, 0.783, and 0.765, respectively. We used the Quiet Quitting Scale (QQS) to measure levels of quiet quitting among nurses [50]. The QQS has a three-factor structure: detachment (four items), lack of initiative (three items), and lack of motivation (two items).…”
Section: Methodsmentioning
confidence: 99%
“…In our study, Cronbach's alpha for the NAQ-R was 0.963. We used the Quiet Quitting Scale (QQS) to measure the levels of quiet quitting among our nurses [25]. The Greek version of the QQS has been validated in a sample of nurses in Greece [26].…”
Section: Methodsmentioning
confidence: 99%
“…A large study in the business sector in the US during the COVID-19 pandemic by Gallup showed that half of the employees are quiet quitters [24]. In the same period, a study of the phenomenon was also initiated in the healthcare sector, with the development of a reliable and valid tool for measuring quiet quitting [25], which revealed that in this sector too, more than 50% of employees opt for quiet quitting, highlighting the urgency of the issue [26]. In particular, nurses had the highest rates of quiet quitting (67.4%) compared to other healthcare professionals [26].…”
Section: Introductionmentioning
confidence: 99%
“…The MDT takes values from 0 to 10 with higher values indicate higher levels of moral distress. Also, we used the "Quiet Quitting Scale" (QQS) to measure levels of quiet quitting among nurses (Galanis et al, 2023e, a). The QQS takes values from 1 to 5 with higher values indicate higher levels of quiet quitting.…”
Section: Methodsmentioning
confidence: 99%